Antiresorptive Agents and Anti-Angiogenesis Drugs in the Development of Osteonecrosis of the Jaw - Allegra, Alessandro; Pulvirenti, Nicolina; Innao, Vanessa; Musolino, Caterina (The Tohoku Journal of Experimental Medicine, 2019)
Medication-related osteonecrosis of the jaw (MRONJ) is a condition of exposed bone in the maxillofacial region, which occurs among subjects treated with antiresorptive agents or anti-angiogenesis drugs, despite the lack of a history of head or neck radiation treatment. Although there are still many points to be clarified about the mechanism of MRONJ, it is possible to hypothesize a common pathogenetic mechanism for two different classes of drugs: antiresorptive and anti-angiogenetic drugs. These drugs can inhibit angiogenesis by interfering with endothelial cell proliferation and survival, leading to loss of blood vessels and avascular necrosis. This hypothesis could be of immediate translational interest. Targeting the anti-angiogenetic effect of the antiresorptive agents could provide a new possibility for the prevention of treatment of MRONJ.